Pituicytoma: Case report of a rare suprasellar tumor - Shashank Mishra; Prerna Guleria (Wolters Kluwer Medknow Publications, 2021)
Pituicytoma is a distinct sellar or supracellar tumor which originates from specialized glial cells of neurohypophyses and infundibulum known as pituicytes. Because of its sellar location patients present with headache, visual disturbance, and endocrine abnormalities. Pituicytoma is difficult to diagnose on neuroimaging as radiological features overlap with other more common tumors of this region. Thus, diagnosis is established by histopathology and immunohistochemistry of resected tumor only. Pituicytomas are composed of bipolar spindle cells arranged as fascicles and are immunoreactive for TTF-1, S100p, and vimentin. These tumors are extremely rare and only around 70 published cases are known in literature. We report a case of suprasellar SOL in a 58-year-old male who presented with headache and gradual visual deterioration in both eyes. He was diagnosed as a case of pituicytoma based on light microscopy findings and immunohistochemical expression of TTF-1, vimentin, S100p, and bcl-2.